Discrete or indiscrete? Redefining the colour polymorphism of the land snail Cepaea nemoralis - Davison, Angus (Heredity (Edinb), 2019)
Biologists have long tried to describe and name the different phenotypes that make up the shell polymorphism of the land snail Cepaea nemoralis. Traditionally, the view is that the ground colour of the shell is one of a few major colour classes, either yellow, pink or brown, but in practise it is frequently difficult to distinguish the colours, and define different shades of the same colour. To understand whether colour variation is in reality continuous, and to investigate how the variation may be perceived by an avian predator, we applied psychophysical models of colour vision to shell reflectance measures. We found that both achromatic and chromatic variation are indiscrete in Cepaea nemoralis, being continuously distributed over many perceptual units. Nonetheless, clustering analysis based on the density of the distribution did reveal three groups, roughly corresponding to human-perceived yellow, pink and brown shells. We also found large-scale geographic variation in the frequency of these groups across Europe, and some covariance between shell colour and banding patterns. Although further studies are necessary, the observation of continuous variation in colour is intriguing because the traditional theory is that the underlying supergene that determines colour has evolved to prevent phenotypes from “dissolving” into continuous trait distributions. The findings thus have significance for understanding the Cepaea polymorphism, and the nature of the selection that acts upon it, as well as more generally highlighting the need to measure colour objectively in other systems.